Imperative Politeness in Learning Interaction at Islamic Institute of Muhammadiyah Sinjai (a Study of Pragmatic Imperative) - Laeli Qadrianti; Nirwana Muhlis (Hasanuddin University, 2019)
This paper aims to examine the form of imperative politeness in the learning interaction Islamic institute of Muhammadiyah Sinjai, the research approach which is used is a qualitative descriptive approach. Instrument data collection through observation, recording and records analyzed using interactive analysis models. The form of imperative politeness found in this study is the Form of Pragmatic Imperative Decency in Declarative Speech and the Form of Pragmatic Imperative Courage in Interrogative Speech. Based on the data obtained, it is known that the form of imperative politeness in the learning interaction Islamic Institut of Muhammadiyah Sinjai consists of five parts, namely: (1) declarative speech which states the pragmatic meaning of imperative orders; (2) declarative speech which states the pragmatic meaning of the invitation imperative; (3) declarative speech which states the pragmatic meaning of the imperative application; (4) declarative speech which states the pragmatic meaning of imperative mating; and (5) declarative utterances which state the pragmatic meaning of the imperative ban. While the form of interrogative politeness in the learning interaction islamic institut of Muhammadiyah Sinjai also consists of five parts, namely: (1) interrogative speech which states the pragmatic meaning of the imperative of the order; (2) interrogative speech that states the pragmatic meaning of the invitation imperative; (3) interrogative speech which states the pragmatic meaning of the imperative application; (4) interrogative speech which states the pragmatic meaning of imperative mating; and (5) interrogative utterances which state the pragmatic meaning of the imperative ban.